Smile Revival: Hollywood Bridge Appliance for the Esthetic Rehabilitation in a Preschooler - Sharma, Shreebindu; Koirala, Bandana; Dali, Mamta; Shrestha, Sneha (Nepal Journal of Health Sciences, 2023)
Dental caries affects people of all ages, often leading to early loss of teeth in children. Early childhood caries starts with the primary maxillary anterior teeth, then primary molars, with about 48% of preschoolers experiencing it worldwide. Rehabilitating a young child with multiple missing teeth due to caries or trauma is a challenging task for any pediatric dentist. Parents often seek aesthetic treatments to preserve their child's appearance and boost their self-confidence. In this case report, a 41⁄2-year-old girl was given a fixed Hollywood bridge appliance, enhancing her appearance, speech, and function while preventing harmful oral habits and boosting her confidence.